Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. The degree to which the supervisory model contributes to enabling the schools of the Oasis Education Office in Jeddah to practice procedural research from the point of view of school employeesMs. Afra Ahmad Shuwaylan, Ms. Hana Mohammed Hussein Abualella, Ms. Aisha Ali Rayih Al-Asmari, Ms. Rasha Ezzat Hussein Ahmed, Ms. Hend Hdyban Al-Jehani2. Women's Attitude Towards Engaging in Sports Activities in The Sultanate of Oman Together towards engaging in sports activities (from Feb to Sep 2023)Ms. Alya Masaud Hamdoon  Alsiyabi3. Challenges of financing higher education in the Kingdom of Saudi Arabia - Taibah University is a modelMs. Enas Moedh Alharbi4. Irrational thoughts as a predictor of depression and burnout in health practitionersMs. Al-Reem Abdullah Al-Owayied, Dr. Saleh Mohammed Al-Rajhi5. The effectiveness of a program based on the Assessment, Evaluation and Programming System (AEPS) in developing social communication skills for children with autism spectrum disorderMr. Laith Emad Al-Ronkose, Prof. Eman Khleif Al-Zboon6. The Emotional Balance and Its Relationship with Social Support among the Elderly in Care Homes in the Governorates of Bethlehem and JerichoMs. Ala Said Abu Haltam, Co-Prof. Fadwa Abdallah Al-Halabiyah7. School Life Quality from the Perspective of Secondary School Students in Arab Schools  in Palestine 1948Ms. Ghadeer Mostafa Abu Khdair, Ms. Areen Khaled Jabarien, Ms. Noran Sohail Igbaria
Keywords: Journal of Educational and Psychological Sciences